Student youth participation in the development of a comfortable urban environment - Yu. V. Ukhanova; A. E. Zhdanova; K. E. Kosygina (Вестник университета)
Currently, the problem of youth participation in the development of urban space is extremely relevant both from the perspective of transforming the living environment with the resources of local communities, and the socialization of urban youth itself, expanding opportunities for personal growth through involvement in socially useful activities. The purpose of the article is to identify the conditions and readiness to participate in the development of a comfortable urban environment for students. The study was conducted in Vologda, Russian Federation, through a quantitative methodological strategy (questionnaire survey among university students, n = 207). The paper presents theoretical and methodological approaches to understanding the urban environment and a comfortable urban environment. It is indicated that a comfortable urban environment is a socio-economic category, reflecting the interactions within the urban space, which is most comfortable for the life of citizens. It is concluded that the student youth expresses their willingness to actively participate in decision-making on the development and improvement of the urban environment. In conclusion, the directions of enhancing the civic participation of young people in the formation of a comfortable urban space on the basis of dialogue platforms are considered.